1984
DOI: 10.1037/0278-6133.3.6.505
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment following ostomy.

Abstract: Ostomy patients have been identified as a chronic illness population frequently experiencing adjustment difficulties. The present study, based on the biopsychosocial model (Engel, 1977) of chronic illness, examined a range of post-surgical adjustment difficulties in a sample of 131 ostomy patients. The patient population reported experiencing a significant number of technical, emotional, social, marital/family, and sexual difficulties post-surgically. Technical difficulties were associated with impaired emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The studies reported important emotional problems as anxiety and depression (McLeod et aL, 1986;Williams and Johnston, 1983;Keltikangas-J~irvinen and J~irvinen, 1987;Thomas et al, 1984Thomas et al, , 1987aWade, 1990), a diminished feeling of self-esteem, feelings of inferiority and shame (MacDonald and Anderson, 1984), serious physical impairment (Foulis and Mayberry, 1990;Williams and Johnston, 1983;MacDonald and Anderson, 1984) decreased self-confidence (Gutman and Reiss, 1985;Foulis and Mayberry, 1990), hopelessness (Keltikangas-J~irvinen and J~irvinen, 1987), and an increased anger and irritation (Follick et aL, 1984;Thomas et al, 1984). The stoma has been marked as a restrictional factor of the social life (Gutman and Reiss, 1985;Foulis and Mayberry, 1990;van de Wiel et aL, 1991;Thomas et al, 1984Thomas et al, , 1987a: Patients appeared to be socially less active and feel restrictions in sports, recreation, travelling, and leisure-time activities.…”
Section: Old Vs Recent Psychosocial Problemsmentioning
confidence: 97%
See 2 more Smart Citations
“…The studies reported important emotional problems as anxiety and depression (McLeod et aL, 1986;Williams and Johnston, 1983;Keltikangas-J~irvinen and J~irvinen, 1987;Thomas et al, 1984Thomas et al, , 1987aWade, 1990), a diminished feeling of self-esteem, feelings of inferiority and shame (MacDonald and Anderson, 1984), serious physical impairment (Foulis and Mayberry, 1990;Williams and Johnston, 1983;MacDonald and Anderson, 1984) decreased self-confidence (Gutman and Reiss, 1985;Foulis and Mayberry, 1990), hopelessness (Keltikangas-J~irvinen and J~irvinen, 1987), and an increased anger and irritation (Follick et aL, 1984;Thomas et al, 1984). The stoma has been marked as a restrictional factor of the social life (Gutman and Reiss, 1985;Foulis and Mayberry, 1990;van de Wiel et aL, 1991;Thomas et al, 1984Thomas et al, , 1987a: Patients appeared to be socially less active and feel restrictions in sports, recreation, travelling, and leisure-time activities.…”
Section: Old Vs Recent Psychosocial Problemsmentioning
confidence: 97%
“…The stoma has been marked as a restrictional factor of the social life (Gutman and Reiss, 1985;Foulis and Mayberry, 1990;van de Wiel et aL, 1991;Thomas et al, 1984Thomas et al, , 1987a: Patients appeared to be socially less active and feel restrictions in sports, recreation, travelling, and leisure-time activities. Impaired partner relationship including nonacceptance by the partner (Follick et al, 1984;Macdonald and Anderson, 1984;La Monica et al, 1985) and sexualproblems are frequently mentioned. Sexual problems include functional problems, such as impotence, problems with ejaculation, and painful intercourse, as well as emotional problems, such as decrease in pleasure, interest, and motivation (Gutman and Reiss, 1985;van de Wiel, 1991;MacDonald and Anderson, 1985;La Monica et aL, 1985).…”
Section: Old Vs Recent Psychosocial Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, men significantly predicted low acceptance {β=−3.078, P=0.023, ΔR 2 =0.036, F [4,117] =7.90, P<0.001} and social engagement score {β=−2.501, P<0.001, ΔR 2 =0.098, F [4,117] =6.03, P<0.001}.…”
mentioning
confidence: 99%
“…In addition to the detrimental effect of cancer itself, most of the colorectal survivors have to deal with ostomy as a part of their treatment (3). Ostomy refers to a surgical procedure that results in an artificial opening in the abdominal wall (stoma) through which bodily waste are excreted (4). To the ostomate, however, it means substantive changes not only in bodily appearance and functional ability but also in overall personal hygiene (5).…”
Section: Introductionmentioning
confidence: 99%